Hematology Profile Analysis and Birth Weight in Preeclampsia - Eko Martanti Listyaning; Aulia Octaviani Dhita; Ariyanti Ida; Prasko Prasko; Adiani Friska (E3S Web of Conferences, 2020)
Preeclampsia is a specific syndrome in pregnancy that occur after 20 weeks gestation in women who were previously normotensive. Hypertension in pregnancy caused complications in cardiovascular, hematology, endocrine, metabolic and regional blood flow accompanied by disorders of various organs, resulting in an increase of hemoconcentration in haemoglobin. The purpose of this study was to analyze the hematology profile and birth weight in preeclampsia. the design of this study was cross sectional with a sample of 40 respondents, consisting of 20 preeclampsia women and 20 women normal pregnancy. The hematology profile assessed was haemoglobin levels, hematocrit levels, platelet levels and blood sedimentation rates. The results showed haemoglobin levels, hematocrit levels, platelet level and blood sedimentation rates in both groups were not significantly difference with p value in each category was 0,110; 0,163; 0,686 and 0,983 (p value >0,05). Thus this study concludes that the hematological profile and birth weight in preeclampsia and normal pregnancies are the same.